Abu Lahab (d. 624) - Kartal, Dilşah Büşra (Bloomsbury Publishing, 2017)
Abu Lahab was the elder brother of Prophet Muhammad's father and was a staunch opponent of Muhammad throughout his life. His full name was Abd al-Uzza Ibn Abd al-Muttalib. He was named Abu Lahab by his father because he had a beautiful face and reddish cheeks. The exact date of Abu Lahab's birth is not known, but he died in 624. Throughout his life, he never wavered in his opposition and role as an enemy of the prophet.